(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the article, thoughts on educating our students in patriotism are put forward. It has been analyzed that educating young students who are the future of our country with high moral qualities, patriotic, humane, physically strong, loving the country, having military knowledge, and the spirit of national pride is the most urgent issue of today. The article can be used by the relevant representatives.